Термінологічна компетентність – важлива складова мовно-комунікативної компетентності сучасного документознавця - Тур, Оксана (Видавництво Львівської політехніки, 2012)
The article analyzes the meaning of "terminological competence" as an important component of language and communicative competence of documentation of contemporary.
Keywords: linguistic and communicative competence; terminological competence of documentation; professional communication; termin